Ca2+ leakage out of the sarcoplasmic reticulum is increased in type I skeletal muscle fibres in aged humans - Lamboley, C. R.; Wyckelsma, V. L.; McKenna, M. J.; Murphy, R. M.; Lamb, G. D. (The Journal of physiology, 2016)
Key points The amount of Ca2+ stored in the sarcoplasmic reticulum (SR) of muscle fibres is decreased in aged individuals, and an important question is whether this results from increased Ca2+ leakage out through the Ca2+ release channels (ryanodine receptors; RyRs). The present study examined the effects of blocking the RyRs with Mg2+, or applying a strong reducing treatment, on net Ca2+ accumulation by the SR in skinned muscle fibres from Old (∼70 years) and Young (∼24 years) adults. Raising cytoplasmic [Mg2+] and reducing treatment increased net SR Ca2+ accumulation in type I fibres of Old subjects relative to that in Young. The densities of RyRs and dihydropyridine receptors were not significantly changed in the muscle of Old subjects. These findings indicate that oxidative modification of the RyRs causes increased Ca2+ leakage from the SR in muscle fibres in Old subjects, which probably deleteriously affects normal muscle function both directly and indirectly. The present study examined whether the lower Ca2+ storage levels in the sarcoplasmic reticulum (SR) in vastus lateralis muscle fibres in Old (70 ± 4 years) relative to Young (24 ± 4 years) human subjects is the result of increased leakage of Ca2+ out of the SR through the Ca2+ release channels/ryanodine receptors (RyRs) and due to oxidative modification of the RyRs. SR Ca2+ accumulation in mechanically skinned muscle fibres was examined in the presence of 1, 3 or 10 mm cytoplasmic Mg2+ because raising [Mg2+] strongly inhibits Ca2+ efflux through the RyRs. In type I fibres of Old subjects, SR Ca2+ accumulation in the presence of 1 mm Mg2+ approached saturation at shorter loading times than in Young subjects, consistent with Ca2+ leakage limiting net uptake, and raising [Mg2+] to 10 mm in such fibres increased maximal SR Ca2+ accumulation. No significant differences were seen in type II fibres. Treatment with dithiothreitol (10 mm for 5 min), a strong reducing agent, also increased maximal SR Ca2+ accumulation at 1 mm Mg2+ in type I fibres of Old subjects but not in other fibres. The densities of dihydropyridine receptors and RyRs were not significantly different in muscles of Old relative to Young subjects. These findings indicate that Ca2+ leakage from the SR is increased in type I fibres in Old subjects by reversible oxidative modification of the RyRs; this increased SR Ca2+ leak is expected to have both direct and indirect deleterious effects on Ca2+ movements and muscle function. Key points The amount of Ca2+ stored in the sarcoplasmic reticulum (SR) of muscle fibres is decreased in aged individuals, and an important question is whether this results from increased Ca2+ leakage out through the Ca2+ release channels (ryanodine receptors; RyRs). The present study examined the effects of blocking the RyRs with Mg2+, or applying a strong reducing treatment, on net Ca2+ accumulation by the SR in skinned muscle fibres from Old (∼70 years) and Young (∼24 years) adults. Raising cytoplasmic [Mg2+] and reducing treatment increased net SR Ca2+ accumulation in type I fibres of Old subjects relative to that in Young. The densities of RyRs and dihydropyridine receptors were not significantly changed in the muscle of Old subjects. These findings indicate that oxidative modification of the RyRs causes increased Ca2+ leakage from the SR in muscle fibres in Old subjects, which probably deleteriously affects normal muscle function both directly and indirectly.